Abortion‐related infections across 11 countries in Sub‐Saharan Africa: Prevalence, severity, and management. (21st January 2022) - Baguiya, Adama; Mehrtash, Hedieh; Bonet, Mercedes; Adu‐Bonsaffoh, Kwame; Compaoré, Rachidatou; Bello, Folasade Adenike; Govule, Philip; Msusa, Ausbert Thoko; Kim, Caron R.; Kouanda, Séni
Abstract: Objective: To estimate the prevalence of infection among abortion‐related complications in health facilities, describe their management, and identify sociodemographic and clinical factors associated with abortion‐related infections. Methods: A secondary analysis of the WHO Multi‐Country Survey on Abortion‐related morbidity (MCS‐A) conducted in 210 health facilities of 11 Sub‐Saharan African countries between 2017 and 2018. The outcome variable was abortion‐related infections, categorized into three mutually exclusive groups of abortion‐related complications: infections only, infection with other complications, and other complications without infection. We described the sociodemographic and clinical characteristics and the management of abortion‐related infection and identified the factors associated with abortion‐related infections using a multinomial logistic model. Results: A total of 9232 women with abortion‐related complications were included, with infection occurring among 10.6% of women ( n  = 974). Infection was involved in 47.4% ( n  = 153) of severe maternal outcomes with a case fatality rate of 27.4% ( n  = 42). The most common management approach was antibiotics, uterine evacuation, and uterotonics combined: 43.2% ( n  = 384) in the group of women with infection only and 48.6% ( n  = 4235) among those with infection and other complications. In addition, 85.9% ( n  = 7095) of women without infection also received therapeutic antibiotics. Factors associated with an increased odds of infection only compared with complication without infection were age younger than 20 years compared with those aged over 30 (aOR 1.84; 95% CI, 1.24–2.74), not living in a couple (aOR 2.05, 95% CI, 1.52–2.76), and gestational age of 13 weeks or more (aOR 1.70, 95% CI, 1.27–2.26). The same factors were associated with infection and other complications. Conclusion: Infection is frequent among severe abortion‐related complications, and its case fatality rate is high. Further research to assess the relationship between abortion‐related infections and outcomes is needed. There is also a need to question the quality of postabortion care and improve adequate use of antibiotics. Synopsis: While abortion‐related infections are not the leading complications, they are more frequent among severe complications and have a higher case fatality rate than other complications.